2022
DOI: 10.1002/cbm.2252
|View full text |Cite
|
Sign up to set email alerts
|

Triarchic psychopathic traits versus self‐control: Comparing associations with youth antisocial outcomes

Abstract: Background: Psychopathy and low self-control are useful constructs for understanding antisociality/criminality. The triarchic model of psychopathy in particular is a recent and promising conceptualisation, composed of boldness, disinhibition, and meanness -three personality traits that have never been studied in tandem with low self-control.Aims: To test relationships between the triarchic personality traits of boldness, disinhibition and meanness and low self-control with delinquent or antisocial acts.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Also, research has found that SC can weaken relationship between psychopathic personality traits and CB among problematic smartphone users by reducing impulsivity and aggression that may be linked with PSY. This indicates that problematic smartphone users with moderate to high SC are less likely to engage in CB, even with PSY personality traits (Pechorro et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Also, research has found that SC can weaken relationship between psychopathic personality traits and CB among problematic smartphone users by reducing impulsivity and aggression that may be linked with PSY. This indicates that problematic smartphone users with moderate to high SC are less likely to engage in CB, even with PSY personality traits (Pechorro et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Within the triarchic model, some have argued that meanness and disinhibition pertain to the most severe forms of psychopathy in criminal offenders and, as such, these traits overlap with Hare’s (2003) four-factor model. In contrast, boldness traits capture interpersonal dominance in noncriminal contexts (e.g., Pechorro et al, 2022) and are less represented in Hare’s model of psychopathy.…”
mentioning
confidence: 99%